Phonon-assisted cooperative energy transfer and frequency upconversion in a Yb3+/Tb3+ codoped fluoroindate glass - Menezes, L. de S.; Maciel, G. S.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 2003)
Phonon-assisted cooperative energy transfer and frequency upconversion (UC) in Yb3+/Tb3+ codoped fluoroindate glass were investigated. Anti-Stokes quasiresonant excitation of Yb3+ ions was used to study the influence of multiphonon transitions in the UC process. A rate equation model was used to describe the temperature dependence of the UC emission intensities and the theoretical results are in good agreement with the experimental data.
Keywords: Glass; Phonons; Terbium; Ytterbium; Frequency upconversion process; Energy transfer